Pengaruh Manajemen Likuiditas terhadap Kinerja Keuangan Perusahaan pada Perusahaan Manufaktur Barang Indonesia - Sihite, Sola Grace Lasmaria; Syarlla Martiza Eka Putri; Nabilah Salma Hersyandana; Henny Setyo Lestari (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the relationship between liquidity management and financial performance. Companies often face challenges in balancing optimal performance with good liquidity management. With this study, it is expected to provide a clearer picture of how much influence liquidity management has on financial performance in the manufacturing sector, as well as provide recommendations that companies can use to improve the efficiency of liquidity management in order to achieve better financial performance. The type of data used is quantitative data and secondary data sources. The sample collection method is purposive sampling. The data testing method is panel data regression analysis. The results show that the current ratio, quick ratio and cash ratio have no effect on financial performance. While the net working capital ratio has an effect on financial performance.